Issues in improving geography and earth science teacher education: results of the #IPGESTE 2016 conference. Issue 3 (3rd July 2019) - Viehrig, Kathrin; Siegenthaler, Daniel; Burri, Samuel; Reinfried, Sibylle; Bednarz, Sarah; Blankman, Marian; Bourke, Terri; Brooks, Clare; Hertig, Philippe; Kerski, Joseph; Kisser, Thomas; Solem, Michael; et al.
ABSTRACT: Earth Science and Geography teacher preparation has developed to some degree along different lines, despite sharing many of the same issues, especially with regard to challenges in teacher education. The conference "International Perspectives on Geography and Earth Science Teacher Education 2016" wanted to bring together educators from both sciences from around the world together to move the debate about these challenges forward. From the research presentations and the discussion during and after the conference, several issues emerged: (1) the importance of the two subjects not losing sight of each other; (2) the need to overcome language barriers; (3) the question of standards/objectives for geography teacher education (e.g. with regard to teachers' (P)CK); (4) media used in teacher education (including ways to improve them); (5) ways to improve learners' geography and earth science content knowledge; and (6) strategies to increase teachers' professionalism. We already suggest some specific steps teacher educators in the two fields can take to improve teacher education. Yet, it also became clear that more research and strengthening international collaborations are needed, as well as better communication of the results of these efforts to practitioners.